Rancang Bangun Aplikasi Bantu Hafal Al-Qur'an Metode At-Taisir Berbasis Android - Nurul Hidayah; Royana Afwani; Andy Hidayat Jatmika (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2019)
The At-Taisir method is a memorization method of the Qur'an which was inaugurated in 2018. This method was initiated by Adi Hidayat and implemented a one-page one-day memorization system of the Qur'an. Usually, when memorizing the Qur'an, the memorizer is flexible in choosing the memorization schedule and memorization amount. But in this method, the memorizer has presented a schedule and amount of memorization so that the memorizer becomes more disciplined and bound. Currently, the activity of memorizing the Qur'an with the At-Taisir method is done manually. This study aims to display the At-Taisir method which was previously still in manual form into a mobile application using Android technology with the native application types. This is expected to make the process of memorizing using the At-Taisir method easier to do without having to wait to get the At-Taisir manuscript first. This application is designed with a dynamic display so that if one day the application wants to be developed again, then only need to add the required database. Based on the results of testing carried out the percentage of success of the application reached 85.9%.